Photodynamic inactivation of drug-resistant bacteria isolated from diabetic foot ulcers - Kashef, N (Tehran University of Medical Sciences, 2011)
BACKGROUND AND OBJECTIVES: Due to the extensive use of antibiotics, the spread of drug-resistant bacteria is one of the most worrisome threats to public health. One strategy that can be used to overcome potential shortcomings might be the inactivation of these organisms by photodynamic therapy. In this study, we have investigated whether drug-resistant wound-associated organisms (Staphylococcus aureus, Staphylococcus epidermidis and Escherichia coli) are sensitive to lethal photosensitization using the dye methylene blue coupled with laser light of 660 nm. MATERIALS AND METHODS: Effect of photosensitizer concentration (25, 50, 100 µg/ml) and laser light dose (27.3, 54.6 and 109.2 J/cm(2)) on lethal photosensitization was investigated. RESULTS: All species were susceptible to killing by photodynamic inactivation. The bactericidal effect was not dependent on the concentration of methylene blue but it was dependent on the light dose. Methylene blue photosensitization using red laser light (109.2 J/cm(2)) was able to achieve reductions of 99.03% and 98.95% in the viable counts of S. aureus and S. epidermidis (using starting concentrations of 10(4)–10(5) CFU/ml). Eradication of 92.23% were obtained for E. coli (initial concentration 10(4)–10(5) CFU/ml) photosensitized by the red light (109.2 J/cm(2)). CONCLUSION: These findings imply that MB in combination with red light may be an effective means of eradicating drug- resistant bacteria from wounds.